WAYS TO EXPAND PUBLIC AWARENESS ON URBAN PASSENGER TRANSPORT - A. Merenkov (Вестник университета, 2016)
The article focuses on evaluating the quality of population awareness. The values of integral quality indicators are calculated to inform passengers about traffic jams, route changes and timetable changes of urban transport. Also produced analysis of modern market of transport mobile apps, improvement recommendations based on the analysis of quality assessment and a new scheme of information services is also provided.